Synthesis and Antibacterial Activity of Polyoxometalates with Different Structures - Jingmin Gu; Lei Zhang; Xiaofeng Yuan; Ya-Guang Chen; Xiuzhu Gao; Dong Li (Bioinorganic Chemistry and Applications)
A new inorganic-organic hybrid compound, [{Cu(phen)2}2(H4W12O40)], was synthesized, and its crystal structure was determined. The Keggin anion H4W12O404− was grafted with two coordination units {Cu(phen)2}, forming an electrically neutral molecule. The antibacterial activity of several polyoxometalate compounds with different anionic structures including the new compound was studied. The results show that the compound 1 can inhibit the growth of Enterococcus faecalis FA2 strains and that antibacterial activity of the polyoxometalate compounds is dependent with component elements of POM but is less relative with the anion structures.